Methods Of Forming Children A Healthy Lifestyle In The Family - Sultanov Alisher Islombaevich (Research Parks Publishers, 2022)
The article describes how children form a healthy lifestyle in the family. On this case, research has been pinpointed both theoretical and methodological aspects of the healthy lifestyle in the families of Uzbekistan. In conclusion, different methods and methodologies have been forwarded to further research points as a whole.